Adipose derived stem cells for bone and cartilage tissue engineering : novel isolation procedure in vitro characterization and in vivo functionality assessment - Rada, Tommaso (2009)
Tese de doutoramento em Ciência e Tecnologia de Materiais (área de conhecimento em Engenharia de Tecidos/Materiais Híbridos)